2(-x-8)=-3(1+x)

Simple and best practice solution for 2(-x-8)=-3(1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-x-8)=-3(1+x) equation:



2(-x-8)=-3(1+x)
We move all terms to the left:
2(-x-8)-(-3(1+x))=0
We add all the numbers together, and all the variables
2(-1x-8)-(-3(x+1))=0
We multiply parentheses
-2x-(-3(x+1))-16=0
We calculate terms in parentheses: -(-3(x+1)), so:
-3(x+1)
We multiply parentheses
-3x-3
Back to the equation:
-(-3x-3)
We get rid of parentheses
-2x+3x+3-16=0
We add all the numbers together, and all the variables
x-13=0
We move all terms containing x to the left, all other terms to the right
x=13

See similar equations:

| 3+m/9=4 | | -17+41=-4(x+1) | | 9x-34=-9x+18 | | 4(x+3)=(x+3)4 | | 295+39x=349+33x | | 15w-3w=4w-2w | | -r+3r=2 | | 5x/3+5=7x/5+3 | | 7/3y+5=26 | | 15+5x=4x+12 | | 5k+1=-9 | | 1m+50=100 | | 2-(1-3c)=2+2 | | 2x+12.41=25.15 | | 2(x+4.5)=15 | | –2q+–1=3 | | k+55/7=-6 | | 4(2x)=180 | | 8/x+9=4/2 | | 1200+30x=1200+50x | | -(n+1)=3 | | 1/2(x+50)=-3x-13+4x | | k=55/7=-6 | | -5(x-2)=2(x+5) | | 25.15=12.41+2x | | 10+10=-5(2x-4) | | 2x-12=7x+10 | | 3^3+12/3*5=s | | 13=(2/5)x | | 1,200+30x=1,200+50x | | 9=-18-b | | 2x10=28 |

Equations solver categories